Everyone Is A Teacher Here Effect on Science Learning Achievement Based on Critical Thinking Skills - Riska Oktalia; Astuti Wijayanti; Tias Ernawati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
This research is a quasi-experiment that aims to know: (1) the difference of science learning achievement between the learning method of everyone is a teacher here with the method of discussion learning (2) the difference of science learning achievement for high and low critical thinking skill (3) the interaction between learning method and the critical thinking skill of the learning achievement of science. Design research using factorial design 2x2. Data collection techniques using test techniques, observation techniques, questionnaires, and documentation. Data analysis techniques for hypothesis testing using a two-way ANOVA test. Based on the results of this research, it can be concluded that: (1) there is a very significant difference the learning outcomes of science between the learning method of everyone is a teacher here with the method of discussion learning (p = 0,000) (2) there is a very significant difference of science learning achievement for high and low critical thinking skills (p = 0,000) and (3) there is a significant interaction between the learning method and the critical thinking skill of the learning achievement (p = 0,040).